Antitubercular Activity of 7-Methyljuglone-Loaded Poly-(Lactide Co-Glycolide) Nanoparticles - Bianca Diedericks; Anna-Mari Kok; Vusani Mandiwana; Bhavna Gowan Gordhan; Bavesh Davandra Kana; Suprakas Sinha Ray; Namrita Lall (MDPI AG, 2024)
Background/Objectives: Loading of natural products into poly-(lactide-co-glycolic) acid (PLGA) nanoparticles as drug delivery systems for the treatment of diseases, such as tuberculosis (TB), has been widely explored. The current study investigated the use of PLGA nanoparticles with 7-methyljuglone (7-MJ), an active pure compound, isolated from the roots of Euclea natalensis A. DC. Methods: 7-MJ as well as its respective PLGA nanoparticles were tested for their antimycobacterial activity against Mycobacterium smegmatis (M. smegmatis), drug-susceptible Mycobacterium tuberculosis (M. tuberculosis) (H37Rv), and multi-drug-resistant M. tuberculosis (MDR11). The cytotoxicity of 7-MJ as well as its respective PLGA nanoparticles were tested for their cytotoxic effect against differentiated human histiocytic lymphoma (U937) cells. Engulfment studies were also conducted to determine whether the PLGA nanoparticles are taken up by differentiated U937 cells. Results: 7-MJ has been shown to have a minimum inhibitory concentration (MIC) value of 1.6 µg/mL against M. smegmatis and multi-drug-resistant M. tuberculosis and 0.4 µg/mL against drug-susceptible M. tuberculosis. Whilst promising, 7-MJ was associated with cytotoxicity, with a fifty percent inhibition concentration (IC50) of 3.25 µg/mL on differentiated U937 cells. In order to lower the cytotoxic potential, 7-MJ was loaded into PLGA nanoparticles. The 7-MJ PLGA nanoparticles showed an 80-fold decrease in cytotoxic activity compared to free 7-MJ, and the loaded nanoparticles were successfully taken up by differentiated macrophage-like U937 cells. Conclusions: The results of this study suggested the possibility of improved delivery during TB therapy via the use of PLGA nanoparticles.